IMPLEMENTASI METODE WATERFALL DAN SYSTEM USABILITY SCALE TESTING PADA APLIKASI FISIOTERAPI PASIEN BPJS - Putra, Budi Permana; Satria, Budy; Murni, Aprilia; Surya, Candra; Sakinah, Putri (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2024)
The background of the problem in this study is that Physiotherapy Services at Permata Hati Hospital for BPJS patients are carried out scheduling or physiotherapy protocol data by writing on the form paper provided and then given to the patient. Besides being given to the patient, the form is also stored by the physiotherapy poly section. The problem that often occurs is that the physiotherapy poly officer must also rewrite the BPJS patient's physiotherapy protocol data in the ledger as data for the next physiotherapy schedule. If you want to find physiotherapy protocol data, it is difficult to do because you have to look one by one in the ledger. The purpose of this research is to make it easier for poly officers to process physiotherapy protocol data in a computerized manner through the design of BPJS patient physiotherapy protocol data applications at Permata Hati Hospital by applying the waterfall method and System Usability Scale (SUS). The results showed that in blackbox testing, the results were obtained in accordance with what was expected starting from the login form test to the patient data input form. Furthermore, testing using the SUS method obtained an average value of 70.75 with a total of 10 respondents and a total of 10 statements. There are 3 components of the System Usability Scale method, namely Acceptable, Grade Scale and Adjective, each component of the results is still at a good value and the level of application is quite comfortable to be used by users.